Fraying at the edge [large type] - Woodsmall, Cindy (Woodsmall, Cindy. Amish of Summer Grove, 2016)
Family, community, faith, and love. These "quilt blocks" sewn together made Ariana's beautiful life. When they are pulled to pieces, will anything familiar remain? The Old Order Amish life Ariana Brenneman loved vanished virtually overnight with the discovery that she was switched at birth twenty years ago. Now she's immersed in the Englischer world, getting to know her mother, and under the authority of her biological father, an atheist intellectual with resolute plans to expand Ariana's worldview. Only Quill Schlabach, a childhood friend living Englisch, can help steady Ariana's tilting ground between the two worlds, but can she trust him after so many betrayals? At the same time, Skylar Nash is forced to choose rehab or spend several months with her true relatives, the large Brenneman family and their seemingly backward life--no electricity, no technology, no fun. What the young woman can't leave behind is her addiction to illegal prescription drugs and deep emptiness from the belief that she doesn't belong in either family. New ties are binding Ariana and Skylar to the lives they were meant to have. Can they pray for the wisdom and strength they'll need to follow God's threads into unexpected futures?